DAMPAK SINKRONISASI BERAHI MENGUNAKAN PROGESTERON TERHADAP BERAHI DAN KEBUNTINGAN SAPI BETINA MILIK RAKYAT KABUPATEN SUKOHARJO - Sutiyono Sutiyono; D. Samsudewa; A. Suryawijaya (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
The aim of this study was to determine the effect of estrus synchronization using progesterone for old heifers and cows of breeder in Sukoharjo District. The research materials were 12 old heifers and 38 cows. The materials of research were synchronized used progesterone hormone on vagina sponge. The hormone progesterone was placing in the vagina and pulled out the sponge on day 18. All estrus heifers and cows were inseminated used frozen semen. The parameter of the research was number of estrus and pregnant. The data obtained were analyzed used Chi-square and statistics of descriptive. The results of the study showed 10 (91.67%) old heifers and 25 (65.79%) cows were estrus. The gestation rate for old heifers and cows showed 4 (44.44 %) and 13 (68.42%), respectively. The chi-square analysis showed highly significant different (P<0.01) for the number estrus between heifers and cows. In other hand, significantly different (P<0.05) were showed for chi-square analysis of pregnancy between heifers and cows. The conclusion The Conclusion, that the success of estrus old heifers not in line with the success of pregnant. Cows are estrus, became pregnant more than old heifers.